Studying Social Development of Students Enrolled in National Outreach Program: A Case Study of Cadet College Hasanabdal - Tariq Javed; Wajiha Kanwal; Tehseen Tahir; Alia Siraj (Journal of Management Practices, Humanities and Social Sciences, 2023)
This study highlighted the social development of less developed areas students enrolled in the National Outreach Program (NOP). The research objective was to know students' perceptions of their social development during the National Outreach Program at Cadet College Hasanabdal. The descriptive survey research design was applied. The 169 male students were taken as a sample of research by using the total population sampling technique. A social development questionnaire was developed by the researcher that was used in this research. The validity of questionnaires was checked through a panel of experts and pilot testing checked reliability. The results indicated that NOP has significantly developed the social skills of students. It can be concluded that NOP is an intervention that paves the path toward an effective learning process. As results indicated a positive change in students due to the NOP in terms of communication skills, building self-esteem, strengthening learning skills, co-curricular activities, and establishing a positive attitude. The national outreach program is run under the Pakistan Institute of Parliamentary Services (PIPS). NOP implies awareness in the fields of civil society, youth, socialization, and engagement. Therefore, it is recommended that government may initiate a NOP program for less developed areas students that facilitates them to acquire social learning skills necessary for their academic success.